Identification of sex characteristics of obesity and hypertension in the adult population of the Vladimir region - M. N. Mamedov; L. T. Sushkova; R. V. Isakov; V. A. Kutsenko; O. M. Drapkina (Российский кардиологический журнал)
Aim. To identify sex characteristics of the prevalence of obesity and hypertension (HTN) in the adult population of the Vladimir region.Material and methods. The study included 1350 people, men and women aged 30-69 years from 5 cities of the Vladimir region (Vladimir, Kovrov, Murom, Yuriev-Polsky and Vyazniki). The response rate was at least 80%. In total, 1174 people completed the study, including 424 men (36,1%) and 750 women (63,9%). The survey was conducted according to a standard questionnaire, including socio-demographic parameters and behavioral risk factors. In all patients, anthropometric parameters, blood pressure, heart rate and resting electrocardiography were assessed.Results. The average body mass index among women was significantly highercompared to men (29,9±6,2 kg/m2 vs 28,3±4,7 kg/m2, p<0,001), while waist circumference among men exceeded similar parameters among women (95,5±11,7 cm vs 91,9±15,3 cm, p<0,001). Sex differences in anthropometric indicators have a number of features in different cities. Every third man is obese, while among women this figure was significantly higher (33,7% vs 42,1%, p<0,001). Every second man and 2/3 of women had abdominal obesity (53,1% and 71,6%, p<0,001). The prevalence of HTN among men and women was comparable (41,5% and 39,9%, respectively). Electrocardiographic signs of left ventricular (LV) hypertrophy are detected in every third respondent, while its prevalence between men and women did not differ statistically (30,5% and 35,5%, respectively).Conclusion. In the surveyed population of men and women of the Vladimir region, the prevalence of obesity and HTN were comparable. The prevalence of obesity and abdominal obesity has sex differences due to the greater severity among women. Hypertension is also highly likely to be associated with LV hypertrophy. Obviously, in order to correct obesity and HTN, lifestyle changes at the population level must be combined with the use of antihypertensive therapy to achieve target blood pressure levels and regress LV hypertrophy.